2012
DOI: 10.1111/j.1365-2761.2012.01362.x
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of Aeromonas schubertii from diseased snakehead, Channa maculata (Lacepède)

Abstract: Pure bacterial cultures were isolated from diseased snakeheads, Channa maculata (Lacepède), suffering high mortality in a farm in Zhongshan, southern China. Three isolates, namely ZS20100725, ZS20100725-1 and ZS20100725-2, were identified as Aeromonas schubertii. All the isolates showed high 16S rRNA sequence similarities with A. schubertii. The isolates exhibited strong virulence to snakeheads in experimental challenges with LD(50) ranging between 1.4 × 10(4) and 6.4 × 10(6) CFU g(-1). Two of the isolates wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
42
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(50 citation statements)
references
References 24 publications
6
42
2
Order By: Relevance
“…The strain LF1708 possesses susceptibility to a wide spectrum of antibiotics including broad‐spectrum sulphonamides, quinolones, chloramphenicols, cephalosporins, aminoglycosides and tetracycline, and resistant to penicillin,ampicillin and lincolmensin. The results are inconsistent with the results obtained from other A. schubertii strains (Chen et al., ; Liu & Li, ). This antibiogram probably demonstrated that the abuse of antimicrobial agents did not occur in the fish farming areas of this outbreak.…”
Section: Discussioncontrasting
confidence: 90%
See 3 more Smart Citations
“…The strain LF1708 possesses susceptibility to a wide spectrum of antibiotics including broad‐spectrum sulphonamides, quinolones, chloramphenicols, cephalosporins, aminoglycosides and tetracycline, and resistant to penicillin,ampicillin and lincolmensin. The results are inconsistent with the results obtained from other A. schubertii strains (Chen et al., ; Liu & Li, ). This antibiogram probably demonstrated that the abuse of antimicrobial agents did not occur in the fish farming areas of this outbreak.…”
Section: Discussioncontrasting
confidence: 90%
“…In the present study, the white spot disease in tilapia typically presents with the similar signs as the disease of snakehead fish caused by A. schubertii in 2012 (Chen et al., ; Liu & Li, ; Liu et al., ), including white nodules in the liver, spleen and kidney. In an interesting manner, it is easy to replicate these typical white nodule signs of naturally occurring disease in experimental challenge but rarely reported on other Aeromonas species infection.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…In 2009, A. schubertii was reported to be an aquacultural pathogen causing internal nodular diseases in the family Channidae and has since spread rapidly throughout China. The pathogen infects the main snakehead species, C. maculata and C. argus , as well as the hybrid cross of C. maculata females × C. argus males, causing high mortality (45%) and becomes one of the most severe diseases in China's snakehead farming industry (Chen, Liang, Zhuo, Wu, & Zou, ; Liu & Li, ; Liu et al., ). This species is also frequently found in other aquatic organisms, including frogs (Pearson, Hirono, Aoki, Miranda, & Inglis, ), shrimp (Yano et al., ), mussels (Latif‐Eugenin, Beaz‐Hidalgo, & Figueras, ) and tilapia (Liu et al., ).…”
Section: Introductionmentioning
confidence: 99%